Corporate investments and environmental regulation: The role of regulatory uncertainty, regulation-induced uncertainty, and investment history. Issue 1 (February 2017) - Rodriguez Lopez, Juan Miguel; Sakhel, Alice; Busch, Timo
Abstract: The relation between uncertainty related to environmental regulation and corporate investments has received considerable attention in the academic literature. Previous quantitative studies, however, have not distinguished between different types of perceived regulation-related uncertainty and do not consider the potential influence of prior investments on firms' investment decisions. Therefore, this paper analyzes how decision makers' perception of two types of uncertainties – regulatory and regulation-induced uncertainty – affects corporate investments in measures to reduce environmental impact. We analyze survey data from a sample of more than 250 companies participating in the EU Emissions Trading System. The data set includes firms from different industries and countries, and covers the first two periods of the trading scheme. Regression results reveal that regulation-induced uncertainty is positively related to a firm's decision to invest, while we find no statistically significant relation to regulatory uncertainty. Moreover, we find that investment history is positively associated with investments in a specific year, but does not moderate the uncertainty–investment relation.